Assessing the net benefits of achieving water quality targets using a bio-economic model. (November 2016) - Beverly, C.; Roberts, A.; Doole, G.; Park, G.; Bennett, F.R.
Abstract: The aim of this study was to develop a bio-economic model to estimate the feasibility and net profit (or net costs) of achieving set water quality targets (sediment, nitrogen, phosphorus and herbicide load reductions) in the Burnett-Mary region within the southern portion of the Great Barrier Reef (GBR), southern Queensland, Australia. Two sets of targets were evaluated, namely (1) Reef Plan Targets (RPTs) representing currently agreed targets, and (2) the more ambitious Ecologically Relevant Targets (ERTs) designed to halt the decline and improve the condition of the GBR. This paper describes the construction of a bio-economic optimisation framework linking field and catchment scale biophysical model results and farm economic analysis to solve for RPTs or ERTs assigned either regionally or within discrete basins. Key outcomes from the study were that RPTs could be achieved whereas ERTs required significant additional investment and were infeasible if individual basins must meet the targets. Highlights: A bio-economic model to evaluate the feasibility of achieving water quality targets is proposed. The bio-economic model was used to help develop a Water Quality Improvement Plan. The bio-economic model is capable to testing the effectiveness of land management options. Some environmental targets cannot be met without substantial costs.